1999
DOI: 10.1192/bjp.174.2.112
|View full text |Cite
|
Sign up to set email alerts
|

Early life family disadvantages and major depression in adulthood

Abstract: Social and family (especially multiple family) disadvantages during childhood predispose individuals to an increased risk of major depression in adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
56
1
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(68 citation statements)
references
References 19 publications
7
56
1
4
Order By: Relevance
“…Overall, in view of the commonly reported associations among depression and early adversities Oakley-Browne, Joyce, Wells, Bushness, & Hornblow, 1995;Sadowski, Ugarte, Kolvin, Kaplan, & Barnes, 1999), the present results are somewhat surprising. The current study suggests that if anything, early experiences were more likely to predict anxiety disorders than depression.…”
Section: Discussioncontrasting
confidence: 53%
“…Overall, in view of the commonly reported associations among depression and early adversities Oakley-Browne, Joyce, Wells, Bushness, & Hornblow, 1995;Sadowski, Ugarte, Kolvin, Kaplan, & Barnes, 1999), the present results are somewhat surprising. The current study suggests that if anything, early experiences were more likely to predict anxiety disorders than depression.…”
Section: Discussioncontrasting
confidence: 53%
“…Other studies have found a link between adult depression and maternal lack of care, family violence, parental marital problems and divorce, family drinking problems and mental illness; studies are generally retrospective or have not focused on midlife women (Kessler & Magee, 1993;Kessler, Davis, & Kendler, 1997;Mullen, Martin, Anderson, Romans-Clarkson, & Herbison, 1994Mullen, Romans-Clarkson, Walton, & Herbison, 1988;Widom, 1998). Two prospective studies from childhood that have followed their subjects into the thirties provide even stronger evidence of a link between adult affective disorders and the early environment (Rodgers, 1990a;Sadowski, Ugarte, Kolvin, Kaplan, & Barnes, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…These disorders include depression, anxiety, drug abuse [11][12][13][14], altered reproductive behavior [15] and compromised learning [16,17]. Many studies have shown that early perinatal procedures in rats can permanently alter various patterns of drug use and behavior in adulthood [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%